PERSEPT 3: A phase 3 clinical trial to evaluate the haemostatic efficacy of eptacog beta (recombinant human FVIIa) in perioperative care in subjects with haemophilia A or B with inhibitors. Issue 6 (6th October 2021) - Escobar, Miguel; Luck, James; Averianov, Yevhenii; Ducore, Jonathan; Fernández, Maria Fernanda López; Giermasz, Adam; Hart, Daniel P.; Journeycake, Janna; Kessler, Craig; Leissinger, Cindy; Mahlangu, Johnny; Martinez, Laura Villarreal; et al.
Abstract: Introduction: Surgical procedures in persons with haemophilia A or B with inhibitors (PwHABI) require the use of bypassing agents (BPA) and carry a high risk of complications. Historically, only two BPAs have been available; these are reported to have variable responses. Aim: To prospectively evaluate the efficacy and safety of a new bypassing agent, human recombinant factor VIIa (eptacog beta) in elective surgical procedures in PwHABI in a phase 3 clinical trial, PERSEPT 3. Methods: Subjects were administered 200 µg/kg (major procedures) or 75 µg/kg eptacog beta (minor procedures) immediately prior to the initial surgical incision; subsequent 75 µg/kg doses were administered to achieve postoperative haemostasis and wound healing. Efficacy was assessed on a 4‐point haemostatic scale during the intra‐ and postoperative periods. Anti‐drug antibodies, thrombotic events and changes in clinical/laboratory parameters were monitored throughout the perioperative period. Results: Twelve subjects underwent six major and six minor procedures. The primary efficacy endpoint success proportion was 100% (95% CI: 47.8%–100%) for minor procedures and 66.7% (95% CI: 22.3%–95.7%) for major procedures; 81.8% (95% CI: 48.2%–97.7%) of the procedures were considered successful using eptacog beta. There was one death due to bleeding from a nonsurgical site; this was assessed as unlikely related to eptacog beta. No thrombotic events or anti‐eptacog beta antibodies were reported. Conclusion: Two eptacog beta dosing regimens in PwHABI undergoing major and minor surgical procedures were well‐tolerated, and the majority of procedures were successful based on surgeon/investigator assessments. Eptacog beta offers clinicians a new potential therapeutic option for procedures in PwHABI.